PENERAPAN SISTEM INFORMASI E-BUSINESS DI INDONESIA: PROSPEK DAN TANTANGAN - Muhammad Anshar Akil (Fakultas Dakwah dan Komunikasi, 2015)
Today the advancement of information and communication technology has brought an enormous impact in many aspects of life, especially the business sector. One of the new concepts on offer is an e-business or electronic business. This business model emphasizes the exchange of information and business transactions are paperless, through Electronic Data Interchange (EDI), e-mail, electronic bulletin boards, electronic fund transfers, and other network-based technology. E-business information system is a device, method, or business methods that utilize technology hardware, software, network, and brainware to interact, transact, and run a variety of business activities across the organization without being limited by time and place. Implementation of e-business information systems have become an important component for organizations to achieve business success nationally and globally. Indonesia considered to be a potential state with the development of e-business or e-commerce the fastest. Nonetheless, the opportunities offered by e-business has not been fully utilized by business organizations.